Pengembangan Sistem Informasi Pemesanan Layanan Jasa Cleaning Service Berbasis Web Dan Mobile Di Liochita Cleaning Semarang - Aulio Romadho Agung; Rinta Kridalukmana; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2016)
Liochita cleaning is a company engaged in the field of cleaning services which are located in the city of Semarang. Until now, the existing of information systems on Liochita Cleaning were not sufficiently able to manage the company and thus to make this company as a company that developed and developing its field and can compete with other companies is not possible. Start from recording customer data and order data, which is the became one as income data, so this companies are less aware in detail of the customer data. On the other hand, customers must make a call in advance to order the services that it requires no small cost. Lack of marketing facilities makes this company unable to include all of costumers in the city of Semarang. Data recording is still using paper, so this company were at risk of paper lost which is containing data that has been recorded . Development of an information system in this study using the method of the waterfall. Waterfall model consists of: requirements, design, implementation, testing and maintenance. For the start of the design, developer need to observations or interviews to determine the needs of the system that being developed. Applications developed using the framework CodeIgniter. The results of this final project is an information system that can meet the needs of Liochita Cleaning in the management of these services, customers and orders in accordance with the business processes that Liochita Cleaning have and allow customers to book services .